A Latent Class Analysis of Intimate Partner Violence (IPV) Experiences in Kosovo - Kelmendi, Kaltrina (Journal of family violence, 2024)
Purpose: Research typically assesses the victimization on the common dichotomist view (indicating whether or not the respondent had experienced any form) of intimate partner violence experiences, and only a few studies examined the overlap of different types of violence victimization in western countries. Using latent class analysis, this study tries to identify the distinct classes of intimate partner violence [IPV] victimization experiences in the Kosovo context. Method: Participants were 325 women (in the 18–40 age range) chosen purposively to participate in the study. Results: This study provided answers to two critical questions: first, if there is an overlap between various types of IPV victimization, and second, if there are distinct patterns that resemble women’s experiences of these co-occurrences. Findings from the study highlight the significant overlap among all four types of violent victimization (physical, psychological, sexual violence, and coercive control). Five classes of women with different experiences of violence were identified: low profile (10.29%), coercive profile (53.46%), emotional profile (24.31%), physical profile (5.34%), and risk profile (6.6%). Conclusion: Evidence from the present study suggests that IPV tends to co-occur and accumulate in this context of low and middle-income countries [LMIC] similar to another context, showing some universality. However, identifying the coercive profile as the largest category through LCA represents a novelty in understanding IPV experiences. Overall, this study shows that a latent subgroup examination promises an effort to better inform prevention and intervention. Recommendations for policymakers to develop screening instruments, early intervention strategies, and programs based on these typologies were discussed.